2016
DOI: 10.1021/acs.jpcc.6b06179
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Modulation on Special Interfacial Magnetic States in Tetragonal La2/3Sr1/3MnO3/BiFeO3 Heterostructures

Abstract: By first-principles calculations on tetragonal La2/3Sr1/3MnO3(LSMO)/BiFeO3(BFO) heterostructures, we demonstrate two interfacial couplings, direct and indirect, for achieving the net Fe moment in the first layer of interfacial regions. The direct Fe–-Mn (indirect Fe+-OB-MnO) exchange couplings induce a net Fe moment of 0.55 μB (−1.07 μB) in MnO2/Fe–O2 (MnO2/O2–Fe) model, which is parallel­(antiparallel) to adjoining Mn around interfaces. Especially, the interfacial net Fe moment in MnO2/Fe–O2 model with 100% s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…The more highly aligned ferroelectric polarization in the T-phase BFO may result in better spin alignment in the CFO phase via strain, leading to the enhancement of the magnetization 34 . An exchange coupling should also be considered, where the reorientation of ferroelectric polarization affects the antiferromagnetic spin distribution inside the BFO phase, which could influence the femimagnetic spin arrangement in the CFO 11,24,35 . Similar enhancements were observed when applying a −9V tip bias, for the [001] and ferroelectric polarizations of the T-phase BFO are actually equivalent.…”
Section: Resultsmentioning
confidence: 99%
“…The more highly aligned ferroelectric polarization in the T-phase BFO may result in better spin alignment in the CFO phase via strain, leading to the enhancement of the magnetization 34 . An exchange coupling should also be considered, where the reorientation of ferroelectric polarization affects the antiferromagnetic spin distribution inside the BFO phase, which could influence the femimagnetic spin arrangement in the CFO 11,24,35 . Similar enhancements were observed when applying a −9V tip bias, for the [001] and ferroelectric polarizations of the T-phase BFO are actually equivalent.…”
Section: Resultsmentioning
confidence: 99%
“…The LAO/STO interface exhibiting metallic properties with the LAO layer larger than 4 unit cell (uc) makes it to have great advantages as nanoscale sensors and controllable channel for nanoelectronic devices. In addition, the novel electronic states at the oxide interfaces have been modulated by various external stimuli, such as electric field, magnetic field, strain, and light . For example, Brown et al discovered a fully reversible conductance change at the LAO/STO interface regulated by LAO surface protonation .…”
Section: Introductionmentioning
confidence: 99%
“…Also LSMO-based heterostructures have been investigated because of the interfacial couplings and intermixing of atoms etc. [2428]. M. Ziese et al reported ferromagnetic order of ultrathin LSMO layers in LSMO/SrRuO 3 superlattices stabilized down to layer thicknesses of at least two unit cells (u.c.)…”
Section: Introductionmentioning
confidence: 99%